Private international law : a Hungarian perspective - Nagy, Csongor István, 1979- (Law in Eastern Europe, 2024)
"This book provides a concise and analytical introduction to private international law in Hungary: international jurisdiction of courts, choice of law (applicable law) and the recognition and enforcement of foreign judicial decisions. It presents both Hungarian conflicts rules and their judicial practice and the application of EU conflicts rules by Hungarian courts"--